1984
DOI: 10.1088/0034-4885/47/3/001
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of methods for thin-film and surface analysis

Abstract: A number of features characteristic of different thin-film analytical methods are reviewed and evaluated.The principles, approaches for quantification and prominent problems of the most commonly used methods (ESCA, AES, SIMS, LEIS, RBS and NRA) are discussed.Evaluation of the special advantages and disadvantages of the different methods points out the need for a synergetic multi-method approach in thin-film analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(24 citation statements)
references
References 705 publications
0
22
0
1
Order By: Relevance
“…It has been suggested that combining these with matrix correction factors leads to an accuracy of -15%. 31 The results of this study indicate that the variability in surface roughness alone can lead to an error approaching 20%. Therefore, unless great care is taken in controlling the effects of surface roughness, through the preparation and analysis of the elemental standards used for determining the sensitivity factors and the analysed sample(s), the attainable accuracy is poor.…”
Section: Discussionmentioning
confidence: 76%
“…It has been suggested that combining these with matrix correction factors leads to an accuracy of -15%. 31 The results of this study indicate that the variability in surface roughness alone can lead to an error approaching 20%. Therefore, unless great care is taken in controlling the effects of surface roughness, through the preparation and analysis of the elemental standards used for determining the sensitivity factors and the analysed sample(s), the attainable accuracy is poor.…”
Section: Discussionmentioning
confidence: 76%
“…The characterization of surface segregation must therefore be not only surface sensitive, but composition to a depth of the order of a few atomic layers becomes essential. At present, these characterization requirements are met to a large extent by analysis techniques based on electron and ion spectroscopies [17][18]. These are Auger electron spectroscopy (AES) [19], angle-resolved X-ray photoelectron spectroscopy or angle-resolved ESCA i.e.…”
Section: Characterizing Surface Segregationmentioning
confidence: 99%
“…3,4 A double focusing type analyzer reduced the secondary beam energy spread. A Faraday cup and electron multiplier detectors were used with ion currents of 10 -8 to 10 -14 A.…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%